2016
DOI: 10.1177/1049909116656353
|View full text |Cite
|
Sign up to set email alerts
|

Can Playing an End-of-Life Conversation Game Motivate People to Engage in Advance Care Planning?

Abstract: Background Advance care planning (ACP) involves several behaviors that individuals undertake to prepare for future medical care should they lose decision-making capacity. The goal of this study was to assess whether playing a conversation game could motivate participants to engage in ACP. Methods: Sixty-eight English speaking, adult volunteers (n=17 games) from communities around Hershey, Pennsylvania and Lexington, Kentucky played a conversation card game about end-of-life issues. Readiness to engage in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 48 publications
1
77
0
Order By: Relevance
“…Van et al also believed that the main obstacles to the low participation rate of ACP included lack of ACP conversation opportunities, avoiding death and dying topics, worrying about the impact of ACP topics on family atmosphere, limited time for clinical staff, and so on. 15 Our results showed that the current life and death discussion topics were not promoted and accepted and lacked the popularization and training of ACP. This may be due to the influence of Chinese traditional culture.…”
Section: Discussionmentioning
confidence: 73%
“…Van et al also believed that the main obstacles to the low participation rate of ACP included lack of ACP conversation opportunities, avoiding death and dying topics, worrying about the impact of ACP topics on family atmosphere, limited time for clinical staff, and so on. 15 Our results showed that the current life and death discussion topics were not promoted and accepted and lacked the popularization and training of ACP. This may be due to the influence of Chinese traditional culture.…”
Section: Discussionmentioning
confidence: 73%
“…Three months post-event, research assistants administered the ACP Engagement Survey by phone and a quantitative questionnaire (Additional ACP Behavior Survey) which was developed based on previous studies of the game intervention. 31 This survey measures nine ACP behaviors not measured in the ACP Engagement Survey (e.g., seeking out information about hospice, obtaining long-term health care insurance) and also opinions about the game conversation (e.g., ''did the game give you a better understanding about ACP or end-of-life issues?'').…”
Section: Three-month Post-game Follow-up Proceduresmentioning
confidence: 99%
“…29,30 Additionally, 70% of participants (with unknown health status) engaged in subsequent ACP behaviors after playing the game. 31 The game has been used successfully in several research settings, including populations of participants with unknown health status in both PA and KY, 29e31 South Asian Indians living in Texas, 32 and chaplainsin-training. 33 Furthermore, the game has been successfully used by in a wide variety of outside organizations (i.e., nonresearch settings) that include religious centers, academic conferences, community festivals, hospice units, and critical care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…812 Barriers for physicians include lack of time and training; barriers for older adults include lack of understanding and wanting to include loved ones who are unavailable or uninterested. 3,13 ACP interventions, such as patient decision aids (eg, websites, videos, card games) 1416 and care models (eg, trained facilitators), 17 have been tested, 18 but the use of these strategies in routine medical care remains limited. 19,20 …”
mentioning
confidence: 99%